ANALISIS FAKTOR YANG MEMENGARUHI PERILAKU ETIS MAHASISWA AKUNTANSI (Studi pada Mahasiswa Akuntansi Perguruan Tinggi di Purwokerto) - Astuti, Mei Wiji; Bangun Kristianto, Giovanny; Saraswati, Esti (J-LEE - Journal of Law, English, and Economics, 2023)
The objective of this study is to examine the partial and simultaneous effects of intellectual intelligence, emotional intelligence, spiritual intelligence, and understanding of the ethical code of the accounting profession on the ethical behavior of college accounting students in Purwokerto. This study is conducted using a quantitative research approach. The sample for this study consisted of 190 students from five universities in Purwokerto. In order to ensure the validity of the analysis, several classic assumption tests were conducted, including normality test, multicollinearity test, and heteroscedasticity test. These tests were performed to assess the distribution of the variables, check for potential collinearity issues among the independent variables, and examine the presence of heteroscedasticity in the data. The data analysis was performed using multiple linear regression technique with SPSS version 25. The findings indicated that intellectual intelligence did not have a significant effect on the ethical behavior of accounting students. However, emotional intelligence, spiritual intelligence, and understanding of the code of ethics of the accounting profession were found to have a positive impact on the ethical behavior of accounting students. Moreover, when considered together, all four independent variables were found to collectively influence the ethical behavior of accounting students.